2023
DOI: 10.3390/diagnostics13142385
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Venous Pressure Gradient Predicts Further Decompensation in Cirrhosis Patients with Acute Esophageal Variceal Bleeding

Abstract: Background: The role of hepatic venous pressure gradient (HVPG) in predicting further decompensation in cirrhosis patients with acute variceal bleeding (AVB) is not known. We aimed to evaluate the role of HVPG in predicting further decompensation in cirrhosis patients with AVB Methods: In this prospective study, 145 patients with cirrhosis with esophageal or gastric AVB were included. HVPG was measured on the day of the AVB. Decompensating events occurring after 42-days of AVB were considered further decompens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Elevated portal vein pressure correlates with a greater degree of esophageal varices. 10–12 The Child-Pugh score is commonly used in clinical practice to assess liver function, 13 , 14 with higher scores indicating worse liver function. Research by Zheng Jin Liu 15 has shown that HVPG values in patients classified as Child-Pugh C are higher than those in class B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated portal vein pressure correlates with a greater degree of esophageal varices. 10–12 The Child-Pugh score is commonly used in clinical practice to assess liver function, 13 , 14 with higher scores indicating worse liver function. Research by Zheng Jin Liu 15 has shown that HVPG values in patients classified as Child-Pugh C are higher than those in class B.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated portal vein pressure correlates with a greater degree of esophageal varices. [10][11][12] The Child-Pugh score is commonly used in clinical practice to assess liver function, 13,14 According to the consensus recommendations, an HVPG level ≥ 16 mmHg indicates a significant risk of complications related to portal hypertension3. In this study, compensated cirrhotic patients with portal hypertension were divided into two groups: those with HVPG < 16 mmHg and those with HVPG ≥ 16 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with decompensated liver cirrhosis and malignant liver tumors, particularly those experiencing gastric variceal bleeding, face a poor prognosis. As discussed in the introduction, gastric variceal bleeding is a leading cause of mortality, primarily due to recurrent bleeding and liver failure ( 17 ). The coexistence of HCC, portal hypertension, and bleeding gastric varices complicates TIPS procedures.…”
Section: Discussionmentioning
confidence: 99%